SN 2011dh: Discovery of a type IIb supernova from a compact progenitor in the nearby galaxy M51 - Arcavi, I; Gal-Yam, A; Yaron, O; Sternberg, A; Rabinak, I; Waxman, E; Kasliwal, M; Quimby, R; Ofek, E; Horesh, A; Kulkarni, SR; Filippenko, A; et al. (2011)
On 2011 May 31 UT a supernova (SN) exploded in the nearby galaxy M51 (the Whirlpool Galaxy). We discovered this event using small telescopes equipped with CCD cameras and also detected it with the Palomar Transient Factory survey, rapidly confirming it to be a Type II SN. Here, we present multi-color ultraviolet through infrared photometry which is used to calculate the bolometric luminosity and a series of spectra. Our early-time observations indicate that SN 2011dh resulted from the explosion of a relatively compact progenitor star. Rapid shock-breakout cooling leads to relatively low temperatures in early-time spectra, compared to explosions of red supergiant stars, as well as a rapid early light curve decline. Optical spectra of SN 2011dh are dominated by H lines out to day 10 after explosion, after which He I lines develop. This SN is likely a member of the cIIb (compact IIb) class, with progenitor radius larger than that of SN 2008ax and smaller than the eIIb (extended IIb) SN 1993J progenitor. Our data imply that the object identified in pre-explosion Hubble Space Telescope images at the SN location is possibly a companion to the progenitor or a blended source, and not the progenitor star itself, as its radius (∼1013cm) would be highly inconsistent with constraints from our post-explosion spectra. © 2011. The American Astronomical Society. All rights reserved..